(untitled) (Heritage, 2020)
In this paper poetry of the poet, professor, Slavist and playwright Boško Suvajdžić is being interpreted, recognizable by the fact that he combines two poetic traditions: folk and medieval, which is nevertheless in the spirit of “modern” singing. With these two lines of his poetry, Suvajdžić also included the third one in the collection of selected and new poetry, Make the Air, which is the subject of our interpretation: elements of the tradition of Minoan culture and civilization, demonstrating that to such an extraordinary creator the framework of national mythology and history are insufficient to express the full extent of his poetic potential and the momentum of the creative imagination; that the poetry is the final hope and final civilization sanctuary to a man who has no place in the world anymore. If this world is not „home for soul“ anymore, it is necessary to “make the air”, to return to the principle according to which, in the poet’s words, we should “be pious and be human.“